3D Interconnected Porous Graphene Sheets Loaded with Cobalt Oxide Nanoparticles for Lithium‐Ion Battery Anodes. Issue 7 (8th April 2016) - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra
Abstract: Nanomaterials with high surface‐to‐volume ratio and tunable electronic and optical properties have expanded their use in variety of applications, especially energy conversion and storage. Here we report on the synthesis of a cobalt oxide (Co3 O4 )/3D‐interconnected porous graphene (PG) nanocomposite by using a simple solvothermal route and its application as a Li‐ion battery anode. Among the different compositions investigated, the composite PG‐600 (with 50 % PG) showed a discharge capacity of 700 mAh g −1 at a current density of 500 mA g −1 and maintained 90 % retention after 80 cycles. The high surface area of the 3D PG sheets helps the Co3 O4 nanoparticles to form a uniform dispersion on the surfaces. The increased surface area (accessibility) and electrical conductivity of the composite result in significant enhancement in the capacity, cycling stability, and rate capability than the native Co3 O4 phase. Abstract : Between the sheets : The authors report on the synthesis of a cobalt oxide (Co3 O4 )/3D‐interconnected porous graphene nanocomposite by using a simple solvothermal route and its application as a Li‐ion battery anode. The Co3 O4 /3D‐graphene composite shows better stability and reversible discharge capacity than the bare Co3 O4 nanoparticle system.